2022
DOI: 10.1002/sstr.202200058
|View full text |Cite
|
Sign up to set email alerts
|

Rechargeable Micro‐Batteries for Wearable and Implantable Applications

Abstract: The rise of wearable and implantable microelectronics calls for the corresponding high‐performance micropower sources. Rechargeable micro‐batteries (MBs) are considered the most promising candidate due to their high energy density and stable voltage output. To date, various MBs with different configurations have been designed to meet the ever‐growing high energy consumption requirements of microelectronic devices. Therefore, it is very urgent to summarize the current challenges of MBs and discuss solutions for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 117 publications
0
19
0
Order By: Relevance
“…Compared with the widespread applications in various flexible and wearable electronics, there is relatively little research on batteries for implantable devices. 61 Implanted electronics are significant in the field of medical applications, which have been mainly powered by LBs since the 1960s. In fact, ZBs may be more suitable for powering these devices due to their intrinsic safety.…”
Section: Biocompatible Zbs For Wearable and Implantable Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the widespread applications in various flexible and wearable electronics, there is relatively little research on batteries for implantable devices. 61 Implanted electronics are significant in the field of medical applications, which have been mainly powered by LBs since the 1960s. In fact, ZBs may be more suitable for powering these devices due to their intrinsic safety.…”
Section: Biocompatible Zbs For Wearable and Implantable Devicesmentioning
confidence: 99%
“…82 A similar technique was exploited for cable-structure batteries, which is based on the solution-extrusion method: the electrode and electrolyte inks would be simultaneously extruded from separated storage tanks into a coagulation bath, in which the hydrogels solidify and wrap the anode and cathode to obtain the flexible battery. 61 During the above assembling process, several parameters should be controlled to present ideal regulations. For example, an excessively large tensile force may result in material fracture, and the lower viscosity of the inks would have an impact on the solidifying and shaping process.…”
Section: Challenges and Issuesmentioning
confidence: 99%
“…Owing to their high power density, flexibility, safety, and low/non‐toxicity, wearable aqueous metal‐air batteries exhibit the promising potential to function as efficient power sources not only in vitro (direct contact to skin) but also in vivo. [ 22,58–61 ] Particularly, wearable aqueous Mg‐air batteries have been considered the most suitable candidates for implantable power sources, due to their good biocompatibility. Huang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their high power density, flexibility, safety, and low/non-toxicity, wearable aqueous metal-air batteries exhibit the promising potential to function as efficient power sources not only in vitro (direct contact to skin) but also in vivo. [22,[58][59][60][61] Particularly, wearable aqueous Mg-air batteries have been considered the most suitable candidates for implantable power sources, due to their good biocompatibility. Huang et al [59] reported that the optimized wearable aqueous Mg-air battery with a high open-circuit voltage of 1.44 V and a peak power density of 5.6 mW cm −2 exhibits stable electrical outputs in vitro and vivo tests, offering a great opportunity for biomedical applications.…”
mentioning
confidence: 99%
“…7 To date, many research advances offered emerging technologies and promising energy solutions to solve the abovementioned challenges. 3,[8][9][10][11] In this review, we discuss the therapy energy demands of different CIEDs in clinic scenarios and the principal design criterion of implantable batteries. We review the evolution and emerging energy solutions for CIEDs, and outlook some promising and cutting-edge technologies for the next-generation CIEDs.…”
mentioning
confidence: 99%